Effects of chemical reaction on magneto-micropolar fluid flow from a radiative surface with variable permeability - Sharma, Bhupendra Kumar; Singh, Ajit Pratap; Yadav, Kailash; Chaudhary, R.C. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a study of a hydromagnetic free convection flow of an electrically conducting micropolar fluid past a vertical plate through a porous medium with a heat source, taking into account the homogeneous chemical reaction of first order. A uniform magnetic field has also been considered in the study which acts perpendicular to the porous surface of the above plate.
Keywords: chemical reaction; micro-polar fluid; micro-rotation; magneto-hydrodynamics; heat transfer; mass transfer